KARAKTERISTIK PERUSAHAAN YANG MEMPENGARUHI PENGUNGKAPAN ASET BIOLOGIS (Perusahaan Agrikultur Yang Terdaftar Di BEI Periode 2020 – 2022) - Miftachul Jannah; Novi Wulandari Widiyanti; Sudarno (KRISNA: Kumpulan Riset Akuntansi, 2024)
Biological assets like plants and animals have unique characteristics that differentiate them from other investments. The importance of disclosing biological assets is reflected in the accounting standard PSAK 69, which emphasizes the need for transparent financial and non-financial information. This research aims to test and analyze the influence of biological asset intensity, company size, ownership concentration, profitability, and leverage on biological asset disclosure. This quantitative research uses the explanatory research method, and the data source used is secondary data obtained from the BEI (Indonesian Stock Exchange) for the 2020-2022 period. The data analysis technique uses the multiple linear regression analysis method, processed using SPSS 25. The research results show that the biological asset intensity variable has a positive effect on biological asset disclosure, the company size variable harms biological asset disclosure, the ownership concentration variable has a positive impact on biological asset disclosure, the profitability variable has a positive effect on biological asset disclosure, and the leverage variable harms biological asset disclosure.